Institusi Normatif dan Substantif Sebagai Poros Kebijakan Edukasi Untuk Menyadarkan Keberagamaan Dalam Pendidikan Islam - Fahruddin, Zuhri (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2022)
People in religion cannot be separated from diversity, especially inter-religious, which has a relatively temporary awareness caused by internal and external impulses so that socio-religious friction occurs in Islamic society, normative and substantive institutions are one that can reduce frictions. Social-religious education through policies issued, on the other hand, Islamic education also indirectly contributes through religious values ​​and norms. This study uses descriptive qualitative data analysis by covering data reduction (data reduction), data presentation (data display), and conclusions or verification (conclusion drawing). With the existence of normative and substantive institutions, policies wisely to stabilize socio-religious friction include the need for a purely vertical and horizontal institutional structure, linearity/consistency between substantive and normative institutions, and comprehensive and maximal in serving inter-religious communities. Keywords: Normative and Substantive Institutions, Religion, Islamic Education